Institutional Leadership in Improving Teacher Performance in Remote Senior High Schools - Tohap; Mada Sutapa (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study examined institutional leadership in improving teacher performance in remote senior high schools. The problem addressed was the persistent gap between leadership policy and teachers' daily professional practice in schools with limited access, infrastructure, and supervisory support. A qualitative multi-site case study was conducted at SMAN 1 Singkup and SMAN 1 Marau through interviews, observation, and document analysis involving principals, vice principals, teachers, and school staff. The findings showed that institutional leadership improved teacher performance when the principal translated school vision into measurable routines, strengthened collegial supervision, protected instructional time, and mobilized local resources. The two schools demonstrated different emphases: SMAN 1 Singkup was stronger in discipline, attendance control, and structured lesson administration, whereas SMAN 1 Marau showed stronger collaborative problem solving and community-based support. The study concluded that teacher performance in remote schools was not determined only by individual competence, but by the quality of institutional arrangements that connected vision, supervision, professional learning, and contextual resource management.